2005
DOI: 10.1016/j.jcrs.2004.10.067
|View full text |Cite
|
Sign up to set email alerts
|

Novel tissue adhesives to secure laser in situ keratomileusis flaps

Abstract: Two novel biodendrimer adhesives successfully sealed and secured LASIK flaps. These adhesives may prove to be an effective alternative for treating LASIK flap complications such as epithelial ingrowth or flap dislocation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…They have also demonstrated the use of the dendritic bio adhesive ([G1]-PGLSA-MA) 2 -PEG in numerous ocular applications including central corneal lacerations [143], clear corneal cataract incisions [144,145], flaps from LASIK surgery [146], scleral incisions [147] and 8-mm penetrating keratoplasties [148]. These in vitro studies tested the capability of this sealant to withstand high IOP (mean leakage pressure of 78.7 mmHg in lacerated cornea) [149].…”
Section: Photo-activated Dendritic Polymersmentioning
confidence: 99%
See 1 more Smart Citation
“…They have also demonstrated the use of the dendritic bio adhesive ([G1]-PGLSA-MA) 2 -PEG in numerous ocular applications including central corneal lacerations [143], clear corneal cataract incisions [144,145], flaps from LASIK surgery [146], scleral incisions [147] and 8-mm penetrating keratoplasties [148]. These in vitro studies tested the capability of this sealant to withstand high IOP (mean leakage pressure of 78.7 mmHg in lacerated cornea) [149].…”
Section: Photo-activated Dendritic Polymersmentioning
confidence: 99%
“…One such adhesive developed consists of lysine-based peptide dendrons with N-terminal cysteine conjugates that react with poly-(ethylene glycol dialdehyde). This formulation was successfully applied for the repair of 3 mm clear corneal incisions [145] and sealing of LASIK flap edges [150] in enucleated eyes.…”
Section: Chemical CXL (Two-component) Dendritic Polymersmentioning
confidence: 99%
“…[16][17][18][19] Using a photocurable hydrogel system based on poly(glycerol-succinic acid)-polyethylene glycol hybrid dendritic-linear macromolecules, full-thickness 4.1 mm corneal lacerations in enucleated eyes and chicken eyes in vivo, as well as secured LASIK flaps in vitro, have been successfully repaired. [19][20][21][22] In addition to light-activated hydrogel formation, other crosslinking strategies that quickly afford a hydrogel adhesive are also explored. [22,23] Herein, we report the synthesis of lysinetermA C H T U N G T R E N N U N G inated peptide dendrimers and dendrons, the formation of crosslinked hydrogels with a poly(ethylene glycol) di-activated ester, the analysis of hydrogel mechanical properties, and the closure of a sclerotomy incision-the wound created during a typical vitrectomy procedure.…”
mentioning
confidence: 99%
“…[19][20][21][22] In addition to light-activated hydrogel formation, other crosslinking strategies that quickly afford a hydrogel adhesive are also explored. [22,23] Herein, we report the synthesis of lysinetermA C H T U N G T R E N N U N G inated peptide dendrimers and dendrons, the formation of crosslinked hydrogels with a poly(ethylene glycol) di-activated ester, the analysis of hydrogel mechanical properties, and the closure of a sclerotomy incision-the wound created during a typical vitrectomy procedure.…”
mentioning
confidence: 99%
“…We have found that crosslinkable derivatives of these dendrimers are useful for the repair of ophthalmic wounds and articular cartilage (35,37,(40)(41)(42). Recently, we described the encapsulation characteristics of a poly(glycerol-succinic acid) (PGLSA) dendrimer and the use of this macromolecule as a potential vehicle for drug delivery (43).…”
Section: Introductionmentioning
confidence: 99%